1967
DOI: 10.1136/bjo.51.3.145
|View full text |Cite
|
Sign up to set email alerts
|

Coats's disease: definition and pathogenesis.

Abstract: IT is remarkable that only one or two writers on Coats's disease appear to have been aware of the fact that Coats had written TWO articles on retinal disease with massive exudation: (1) his primary paper which appeared in the English language (1908), and (2) his final article which was published 4 years later (1912) in the German language. In the second paper, which has apparently been overlooked by most students of Coats's disease, the author gave evidence that his opinion had changed somewhat in the interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Ophthalmoscopic exam¬ ination revealed bilateral peripheral telan¬ giectasis but no posterior pole disease. Fluorescein angiographie examination (April 13,1984) confirmed bilateral telan¬ giectasis, with abnormal fluorescein leak¬ age and areas of capillary closure (Fig 2).…”
Section: Report Of Casesmentioning
confidence: 99%
“…Ophthalmoscopic exam¬ ination revealed bilateral peripheral telan¬ giectasis but no posterior pole disease. Fluorescein angiographie examination (April 13,1984) confirmed bilateral telan¬ giectasis, with abnormal fluorescein leak¬ age and areas of capillary closure (Fig 2).…”
Section: Report Of Casesmentioning
confidence: 99%
“…Many investigators studied infectious, inflammatory, metabolic, and other aetiologies, and some suggested different names for this condition 6. Three, several other local and systemic disease processes can produce retinal exudation, and many publications as late as the 1960s included very different disease processes under a slightly different rubric, Coats' disease 7. In addition, Coats' disease has been described as a syndrome in association with several hereditable ocular diseases including retinitis pigmentosa, Hallermann–Streiff syndrome, Senior–Loken syndrome, Cornelia De Lange syndrome, Parry–Romberg syndrome and the epidermal naevus syndrome 8-13…”
mentioning
confidence: 99%
“…This description was later revised to exclude retinal hemorrhage [2][3] and to include bilaterality [4][5][6]. In the earlier stages of the disease externally applied diathermy [4,7], laser photocoagulation or cryotherapy alone may be effective in destroying the retinal telangiectasia [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%